2021
DOI: 10.1371/journal.pntd.0009651
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community factors determining delayed leprosy case detection: A systematic review

Abstract: Background The number of new leprosy cases is declining globally, but the disability caused by leprosy remains an important disease burden. The chance of disability is increased by delayed case detection. This review focusses on the individual and community determinants of delayed leprosy case detection. Methods This study was conducted according to the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The study protocol is registered in PROSPERO (code: CRD42020189274). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
5
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 59 publications
5
59
5
9
Order By: Relevance
“…A higher mean delay in case detection was reported by Deps et al (2006), Engelbrektsson et al (2019), and Gomez et al (2018) of 25.3 months in Brazil, 29.8 months in Nepal and 33.5 months in Colombia respectively [ 39 , 41 , 42 ]. A recent literature review on detection delay by Dharmawan et al (2021) found a mean delay ranging from 11.5 to 64.1 months [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher mean delay in case detection was reported by Deps et al (2006), Engelbrektsson et al (2019), and Gomez et al (2018) of 25.3 months in Brazil, 29.8 months in Nepal and 33.5 months in Colombia respectively [ 39 , 41 , 42 ]. A recent literature review on detection delay by Dharmawan et al (2021) found a mean delay ranging from 11.5 to 64.1 months [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definition for delayed diagnosis, or prolonged delay in case detection, varies in the literature; six months is referred to as a “long delay”, but some studies advocate for shorter periods of time [ 32 , 42 , 44 ]. Consequently, Dharmawan et al (2021) propose a threshold of 6 or 12 months as a uniform definition for detection delay in leprosy [ 43 ]. This is in line with the cut-off point of 12 months which was used in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…Leprosy is associated with social inequality and precarious socioeconomic conditions, making access to treatment and health services difficult [5,6]. Primary care health actions can minimise the damage of social inequality present in endemic scenarios of the disease through comprehensive healthcare planning that prioritises the particularities of each territory [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Social and health inequalities present in endemic scenarios for leprosy are obstacles for populations to access health systems and services, which favour illness and disease complications and hinder timely diagnosis, adequate treatment and prevention of physical disabilities and deformities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Os principais sinais e sintomas da hanseníase são: áreas da pele, ou manchas esbranquiçadas (hipocrômicas), acastanhadas ou avermelhadas, com alterações de sensibilidade ao calor e/ou dolorosa, e/ou ao tato; Formigamentos, choques e câimbras nos braços e pernas, que evoluem para dormênciaa pessoa se queima ou se machuca sem perceber; Pápulas, tubérculos e nódulos (caroços), normalmente sem sintomas; Diminuição ou queda de pelos, localizada ou difusa, especialmente nas sobrancelhas (madarose); Pele infiltrada (avermelhada), com diminuição ou ausência de suor no local (Fragozo-Ramos et al; Dharmawan et al,2021).…”
unclassified